Anticorrosive properties of electrosynthesized poly(o-anisidine) coatings on copper from aqueous salicylate medium - Chaudhari, Sudeshna; Sainkar, S. R.; Patil, P. P. (Journal of Physics D-Applied Physics, 2007)
Poly( o-anisidine) ( POA) coatings were electrosynthesized on copper ( Cu) from an aqueous solution containing o-anisidine and sodium salicylate by using cyclic voltammetry, galvanostatic and potentiostatic modes. The extent of corrosion protection offered by these coatings to Cu in aqueous 3% NaCl solution was evaluated by the open circuit potential measurements, potentiodynamic polarization technique and electrochemical impedance spectroscopy. Potentiodynamic polarization and electrochemical impedance spectroscopy studies reveal that the POA acts as a protective layer on Cu against corrosion in 3% NaCl solution. The positive shift in the corrosion potential for the POA-coated Cu indicates the protection of the Cu surface by the POA. The POA coating synthesized by using cyclic voltammtery, galvanostatic and potentiostatic modes reduces the corrosion rate of Cu almost by a factor of 100, 100 and 7, respectively. The cyclic voltammetry was proved to be the better mode to adopt for the synthesis of more compact and strongly adherent POA coatings on Cu. The coatings synthesized by this mode were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. It was found that the electrochemical polymerization of o-anisidine on Cu takes place after the passivation of its surface via the formation of Cu2O and/or copper salicylate complex and results in the generation of shiny, uniform and strongly adherent POA coatings. The optical absorption spectroscopy reveals the formation of the emeraldine salt form of POA. The results of this study clearly ascertain that the POA has outstanding potential to protect Cu against corrosion in a chloride environment.